Données ouvertes liées et recherche historique : un changement de paradigme - Francesco Beretta (Humanités Numériques)
In the context of the digital transition, the semantic Web and linked open data (LOD) play an increasingly central role as they allow the construction of knowledge graphs linking together the resources of the Web. This phenomenon questions the historical sciences and raises the major issue of a paradigm shift. After clarifying what the meaning of “data” is, the paper analyses their place in the process of knowledge production. It presents the main components of the paradigm shift, and in particular the potential of LOD and robust semantics as vehicles for high-quality, intelligible and reusable factual information. We then present the infrastructure projects carried out at the Larhra (Laboratoire de recherche historique Rhône-Alpes) with the aim of facilitating the digital transition: symogih.org, ontome.net, geovistory.org. These Web applications are developed in line with the epistemology of the historical sciences and contribute to the realisation of a disciplinary “information graph”.